A sub-kiloparsec-scale view of un-lensed submillimeter galaxies. Issue Volume 15:Issue S352(2019) (June 2019) - Tadaki, Ken-ichi; Iono, Daisuke
Abstract: Submillimeter galaxies at z > 3 building up their central cores through compact starbursts with an effective radius of 1–2 kpc. Our ALMA high-resolution observations reveal off-center gas clumps in a submillimeter galaxy at z = 4.3, COSMOS-AzTEC-1, as well as a rotation-dominated disk. Exploiting the kinematic properties and the spatial distribution of gas mass surface density, we find that the starburst disk is gravitationally unstable. This result is consistent with a scenario where in-situ clumps are formed through disk instability. On the other hand, we find evidence for an ex-situ clump that does not corotate with the starburst disk. The accretion of such a non-corotating clump could stimulate violent disk instability, driving gas inflows into the central regions of the galaxy. Our results suggest that compact cores are formed through an extreme starburst due to a gravitational instability, triggered by non-corotating clumps.